Pathophysiological Concepts of Constrictive Pericarditis in Cardiac Imaging: Back to Basics. (6th May 2021) - Vucic, Esad; Chakhtoura, Elie Y.; Sohal, Sumit; Waxman, Sergio
Abstract : Supplemental Digital Content is available in the text.